Network Model of Local Development Planning: Case of Local Development Planning Forum in Bone Regency - Nani Harlinda Nurdin; Alwi Alwi2 (Iapa Proceedings Conference, 2019)
The complexity of development that occurs in development problems where stakeholders have difficulty in determining problems and finding solutions to these problems. This is due to the many actors involved with different needs and interests, so that the results of development are not of many benefits received by all levels of society. Musrenbang as a local development planning forum identified in this study as an network organization of local development planning, aims to encourage the involvement of stakeholders in designing local development planning programs. This study aims to develop a network model of local development planning in Bone Regency. The research uses a qualitative approach and consists of primary data and secondary data. The data collected is then processed throught data reduction. The results of the study show that the network model of local development planning has not been implemented, as can be seen from the absence of development programs oriented to the community, especially the poor. This shows the high level of poverty in Bone Regency.